Evaluación de cuatro sustratos en la multiplicación de variedades de Menta (Mentha piperita y Mentha espicata) - Enríquez Benavides, Darwin Hernando (2017)
VIII. SUMMARY dddd This work was located in the Santa Clara, Parish González Suárez Urban sector of the city of San Gabriel, cantonal head of Montufar. It is located at the following coordinates 00 ° 35 '58.5 "north latitude and 77 ° 50' 17.1" west longitude at an altitude 2,902 meters. Weather conditions in the area show an annual average: 800 mm rainfall, temperature 12th C and a relative humidity of 80%. The living areas is configured with natural vegetation and forest remnants, grasslands, heaths or moors where the degree of human intervention is very low and predominantly natural vegetation, so we have the highest logged forest evergreen montane evergreen forest upper montane, wet moor, heath shrub, montane lake grassland, moor frailejones, natural grass, dry herbaceous vegetation. Has a clay loam soil: They are soils with clay, sand, organic matter, they reach a depth of 1 to 3 m; its color is black with pH of 5.5 to 6.5. The genetic material used was of origin in the same area of study (Mentha piperita) and (Mentha spicata). The treatments carried out in the research project were eight, which resulted from the combination of Factor A Variety; 1: (Mentha piperita) 2: (Mentha spicata and Factor B, Substrates; 1 (50% sand rivers + 25% humus + 25% land moor), 2 (50% Pomina + 25% Abonaza + 25% land of moor ) 3 (50% rice husks + 25% peat + 25% land of paramo);.. 4 ground site Design Randomized Complete (DBCA) in a factorial arrangement (AXB) with 3 replications blocks was applied All variables were subjected to analysis of variance was used the Duncan test at 5% probability. he variables were evaluated; nutritional analysis of the substrates, percent germination, sprout length, root weight, total weight of the plant and economically analyze the treatments. According to the results it was determined that in varieties; Mentha piperita presented average higher in variables; bud length, root weight and total weight of the plants, in the substrates was recorded averages above compound (river sand + humus + moor land) is variables; germination percentage, long tota sprouts, root weight and total weight of the plant. In the treatment of (Mentha piperita variety, with river sand + humus + moor land), average log in significant variables; germination percentage, shoot length, root weight and total weight, but treatment A2-B1 (Mentha spicata, with river sand + humus + moor land), showed similar results; germination percentage, shoot length and root weight. Thus increased production and quality plants in the two varieties with the substrate (river sand + humus + moor land) was obtained. In itself the greatest economic usefulness with treatment A1-B1 (Mentha piperita variety, with river sand + humus + moor land) of 3.097,99 USD / 50 m2 was obtained.